COMPARATIVE ANALYSIS OF GAMMA RAY DOSE BUILDUP FACTOR CALCULATION METHODS IN AIR (American Journal of Pedagogical and Educational Research, 2024)
The dosage buildup factors for gamma rays in air are thoroughly examined in this work using four different formulations: the linear, quadratic, Berger, and Capo forms. We compute the accumulation factors and analyze their behavior as a function of the number of mean free pathways, using isotope data and attenuation coefficients. At lower photon energy, the data indicate notable variances, especially between the linear and Capo forms; at higher energies, there is convergence. Furthermore, for photon energies of 0.04, 0.38, and 1.09 MeV under various stability classes and release heights (20 m and 100 m), we examine gamma doses as a function of downwind distance. The results offer important insights into gamma radiation and emphasize the significance of choosing suitable buildup factor formulations depending on photon energy.